Configuring the nature of colonial hospital architecture in peninsular Malaysia-serie 1- Special studies on the tuberculosis ward and hospital administration building typologies of Kota Bharu Hospital - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Denan, Zuraini; Abdul Rahim, Zaiton; Ismail, Azrul Izwan (2010)
Colonial hospital architecture in Malaysia is one of the forgotten built heritages in the country. The embarkation of this multifaceted research in haste is due to the Ministry of Health Malaysia’s upgrading development of the country’s healthcare facilities asset throughout the country under the 9th Malaysia plan that requires demolition and reuse of existing hospitals for new healthcare services and infrastructure. Colonial era hospitals are known intuitively for its tropical and “user friendly” architecture that addresses the local climatic requirements and local culture for ease in visitation. The use of local timber and other building materials were made to last in comparison to today’s quality of 50 year lifespan. Although they lack the latest technology in providing convenience of today’s definition of “comfort” and “healing environment”, their simplicity in addressing healthcare needs of the local populace integrated with nature indeed demand thorough research before all is lost. The research aims to collect available physical data and historical record of the facilities in digital and manual form so as to be able to extrapolate for further research on its effectiveness in previous and current environment in terms of the following issues: (i) micro medical planning and healthcare requirement then and now, (ii) building configuration and comparison to other colonial hospital building at home and abroad, (iii) spatial provisions and standards (iv) building material (v) construction and material detailing (vi) environmental consideration (vii) user considerations – culture, gender, ethnic group. The methodology use for this research includes literature review, measured drawing, interview, laboratory studies (environmental) and computer modeling; in collaboration with the industry players (MoH, JKR and consultants) Significance of the research are (i) direct contribution to the green building agenda of the government not only for healthcare building; (ii) historical data in healthcare architecture (iii) infection control strategies then and (iv) cultural significance to local populace.